14th Nordic-Baltic Conference on Biomedical Engineering and Medical Physics NBC 2008. 16-20 June 2008. Riga, Latvia - Katashev, Alexei (IFMBE Proceedings,, 2008)
14th Nordic – Baltic Conference on Biomedical Engineering and Medical Physics NBC 2008 brought together scientists not only from the Nordic – Baltic region, but from the entire world. This volume presents the Proceedings of this international conference, jointly organized by the Latvian Medical Engineering and Physics Society, Riga Technical University and University of Latvia in close cooperation with International Federation of Medical and Biological Engineering (IFMBE) The topics covered by the Conference Proceedings include: Biomaterials and Tissue Engineering; Biomechanics, Artificial Organs, Implants and Rehabilitation; Biomedical Instrumentation and Measurements, Biosensors and Transducers; Biomedical Optics and Lasers; Healthcare Management, Education and Training; Information Technology to Health; Medical Imaging, Telemedicine and E-Health; Medical Physics; Micro and Nanoobjects, Nanostructured Systems, Biophysics.